2021
DOI: 10.1002/ece3.7269
|View full text |Cite
|
Sign up to set email alerts
|

3D genital shape complexity in female marine mammals

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…These findings are in line with previous studies that applied alpha shapes to genital form, which also found consistency between complexity scores and informal qualitative observations (Gardiner et al, 2018;Orbach et al, 2021). Indeed, all species in the family Lutrinae are grouped with low PC1 scores, commensurate with their 'simple' shape at both coarse and fine scales.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in line with previous studies that applied alpha shapes to genital form, which also found consistency between complexity scores and informal qualitative observations (Gardiner et al, 2018;Orbach et al, 2021). Indeed, all species in the family Lutrinae are grouped with low PC1 scores, commensurate with their 'simple' shape at both coarse and fine scales.…”
Section: Discussionsupporting
confidence: 91%
“…Models in Collection 1 were stored in a 3D voxel format, and the points clouds were produced by taking the row, column and depth of each voxel's location as the x, y and z coordinates respectively and randomly down-sampling to 100,000 points. Previous analyses [30,21,31] have found 100,000 points to be a good compromise between retaining sufficient detail of the original model and minimising calculation times. The volume of each model in Collection 1 was calculated as the sum of the number of voxels in the original model.…”
Section: Alpha-shape Complexity (J Gardiner and Cmentioning
confidence: 99%
“…Alpha-shape complexity algorithm. Once model point clouds, and their associated volumes and reference lengths, had been calculated, the alpha-shape complexity algorithm (originally developed for analysing biological datasets lacking homologous landmarks [30,21,31]) was run. Alpha-shapes [32] are a suite of shapes fitted to underlying point clouds, with the 'tightness' of their fit being determined by the value of the radius α.…”
Section: Alpha-shape Complexity (J Gardiner and Cmentioning
confidence: 99%
“…Additional difficulty is that a large part of the relevant anatomical literature was published in German (and perhaps other languages), such that a large knowledge base is difficult to access for many researchers. As these and other reasons for the lack of attention to clitoral anatomy are being increasingly overcome in recent decades, we observe intensified research into the details of the female reproductive anatomy, its function and evolution ( Puppo 2013 ; Cunha et al 2014 ; Lima et al 2015 ; Pavlicev and Wagner 2016 ; Sinclair et al 2017 ; Orbach et al 2019 ; Pavlicev et al 2019 ; Levin 2019 ; Orbach et al 2021 ; Brennan et al 2022 ). To further foster this direction of research, we aim at summarizing the comparative anatomical information currently available.…”
Section: Introductionmentioning
confidence: 99%